Analyzing Translation Techniques Used in Sesame Street Books - Murniati Murniati (Universitas Bunda Mulia, 2017)
This article discusses how have the English Sesame Streets books been translated into Indonesian. The source language had to be very carefully translated into the target language, in this case is Indonesian, since the readers are very young. Data were taken from five bilingual Sesame Street books for toddlers. They were analyzed by using translating techniques by Hoed (2006). The results showed that seven techniques were used and successfully conveyed the meaning and style from the source language to the target language. Keywords: source language, target language, translation techniques